Reconstruction and analysis of the DAN5/P1 and BSN12/P1 Gona Early Pleistocene Homo fossils. Issue 162 (January 2022) - Baab, Karen L.; Rogers, Michael; Bruner, Emiliano; Semaw, Sileshi
Abstract: Two Early Pleistocene fossils from Gona, Ethiopia, were originally assigned to Homo erectus, and their differences in size and robusticity were attributed to either sexual dimorphism or anagenetic evolution. In the current study, we both revisit the taxonomic affinities of these fossils and assess whether morphological differences between them reflect temporal evolution or sexual variation. We generated virtual reconstructions of the mostly complete ∼1.55 Ma DAN5/P1 calvaria and the less complete 1.26 Ma BSN12/P1 fossil, allowing us to directly compare their anterior vault shapes using landmark-based shape analysis. The two fossils are similar in calvaria shape to H. erectus and also to other Early Pleistocene Homo species based on a geometric morphometric analysis of calvaria landmarks and semilandmarks. The DAN5/P1 fossil bears a particularly close affinity to the Georgian H. erectus fossils and to KNM-ER 1813 ( H. habilis ), probably reflecting allometric influences on vault shape. Combined with species-specific traits of the neurocranium (e.g., midline keeling, angular torus), we confirm that these fossils are likely early African H. erectus . We calculated regression-based estimates of endocranial volume for BSN12/P1 of 882–910 cm 3 based on three virtual reconstructions. Although BSN12/P1 is markedly larger than DAN5/P1 (598 cm 3 ), both fossils represent the smallest adult H. erectus known from their respective time periods in Africa. Some of the difference in endocranial volume between the two Gona fossils reflects broader species-level brain expansion from 1.77 to 0.01 Ma, confirmed here using a large sample ( n  = 38) of H. erectus . However, shape differences between these fossils did not reflect species-level changes to calvaria shape. Moreover, the analysis failed to recover a clear pattern of sexually patterned size or shape differences within H. erectus based on our current assessments of sex for individual fossils. Highlights: Neurocranial shape of Gona Pleistocene fossils supports assignment to Homo erectus. Neurocranial shape in H. erectus does not map onto hypothesized sex differences. Expanded data set confirms brain expansion in H. erectus between 1.8 and 0.1 Ma.